2012
DOI: 10.1093/jxb/ers273
|View full text |Cite
|
Sign up to set email alerts
|

The Brassica napus Calcineurin B-Like 1/CBL-interacting protein kinase 6 (CBL1/CIPK6) component is involved in the plant response to abiotic stress and ABA signalling

Abstract: A CBL-interacting protein kinase (CIPK) gene, BnCIPK6, was isolated in Brassica napus. Through yeast two-hybrid screening, 27 interaction partners (including BnCBL1) of BnCIPK6 were identified in Brassica napus. Interaction of BnCIPK6 and BnCBL1 was further confirmed by BiFC (bimolecular fluorescence complementation) in plant cells. Expressions of BnCIPK6 and BnCBL1 were significantly up-regulated by salt and osmotic stresses, phosphorous starvation, and abscisic acid (ABA). Furthermore, BnCIPK6 promoter activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 44 publications
2
84
0
Order By: Relevance
“…By contrast, double- cbl2/cbl3 -mutant plants were found more resistant to high Na + and low K + conditions (Tang et al, 2012). Similar stress responses of CBLs have also been reported in rice OsCBL8 (Xiang et al, 2007), Ammopiptanthus mongolicus AmCBL1 (Chen et al, 2011), soybean GmCBL1 (Li et al, 2012), rape BnCBL1 (Chen et al, 2012), and tobacco NsylCBL10 (Dong et al, 2015). Ten CBL proteins have also been discovered in Arabidopsis , rice and populous (Albrecht et al, 2001; Kolukisaoglu et al, 2004; Zhang et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
“…By contrast, double- cbl2/cbl3 -mutant plants were found more resistant to high Na + and low K + conditions (Tang et al, 2012). Similar stress responses of CBLs have also been reported in rice OsCBL8 (Xiang et al, 2007), Ammopiptanthus mongolicus AmCBL1 (Chen et al, 2011), soybean GmCBL1 (Li et al, 2012), rape BnCBL1 (Chen et al, 2012), and tobacco NsylCBL10 (Dong et al, 2015). Ten CBL proteins have also been discovered in Arabidopsis , rice and populous (Albrecht et al, 2001; Kolukisaoglu et al, 2004; Zhang et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
“…MPK genes were reported to participate in response to cold, drought, ultraviolet light, oxidation stress and disease in many crops [4547]. Thirdly, CBL7 , as one of the plant calcium sensors, can interact with CIPKs to form CBL-CIPK complexes that mediate responses to salinity, drought stress, phosphorous deficiency and ABA signaling [4850]. Li et al [49] indicated that over-expression of soybean CBL1 enhances tolerance to salinity and drought stress in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the top-ranked classic HKGs such as eEF1-␣ and UBC10, the actin and rRNA gene are also used for normalizing stress-responsive genes in a wide range of species, including soybean, rice, and Brassica napus L. (Chen et al 2012;Nakashima et al 2007;Novillo et al 2012;Yan et al 2011;Zhou et al 2010). However, normalization by the less stably expressed 25S rRNA showed distinct differences in expression results for the target CBF-like gene compared with normalization using the eEF1-␣ and UBC10 genes, with low expression levels and weaker variation observed for the target gene (Fig.…”
Section: Discussionmentioning
confidence: 99%